Between hope and hype: Traditional knowledge(s) held by marginal communities - Rapti Siriwardane; Sarah Winands (University of Bonn, Center for Development Research (ZEF), 2013)
Traditional Knowledge (TK) systems have always been integral to the survival and adaptation of human societies. Yet, they enjoy a fairly recent recognition and popularization by scientists, the media, politicians, corporates and the wider public. In this paper we present a typology of key driving forces behind the popularization of TK held by marginal communities: an equality preference motive, a value motive, a compliance motive, a scarcity motive and a strategic motive. Secondly, through the use of a simple model, we discuss the hype's impact on marginal communities. Moreover, we critically assess the outcome of a number of policy instruments that intend, in part, to protect traditional knowledge bases of such communities. Our analysis primarily draws upon secondary literature; policy documents and case studies within economics, the social sciences, conservation biology and legal studies. We argue that whilst the public and institutional hype around TK may have resulted in its prioritization within international conventions and frameworks, its institutionalization may have adversely impacted marginalized communities, and in particular contexts, unintentionally led to the creation of 'new' marginals. We purport that the traditional innovation incentive motive does not hold for protecting TK within a private property regime. Instead we identify a conservation incentive motive and a distribution motive that justify deriving policy instruments that focus on TK to protect marginal communities.
Keywords: 330; traditional knowledge; marginality; common property regime; social welfare; community participation